2009
DOI: 10.1534/genetics.108.093708
|View full text |Cite
|
Sign up to set email alerts
|

Ancient Trans-specific Polymorphism at Pheromone Receptor Genes in Basidiomycetes

Abstract: In the majority of sexual organisms, reproduction occurs almost exclusively through the combination of distinct and alternate forms, called sexes or mating types. In some fungi, there can be dozens to hundreds of alternate alleles that determine compatible mating types. Such extensive polymorphism is expected to be maintained by balancing selection, and in extreme cases may give rise to trans-specific polymorphism. Here, we analyzed sequences of two pheromone receptors in the Microbotryum fungal species comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
105
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(106 citation statements)
references
References 79 publications
1
105
0
Order By: Relevance
“…A1 and STE3.A2), and the presence of each allele is always correlated with the mating behavior (Devier et al 2009;Coelho et al 2011). The same holds true for the L. scottii species complex (de Garcia et al 2015) ( Figure 3A), thus showing that pheromone receptor genes are useful markers of mating-type identity across a broad range of Pucciniomycotina species.…”
Section: Mat Allele Diversity In the L Scottii Species Complexmentioning
confidence: 65%
See 1 more Smart Citation
“…A1 and STE3.A2), and the presence of each allele is always correlated with the mating behavior (Devier et al 2009;Coelho et al 2011). The same holds true for the L. scottii species complex (de Garcia et al 2015) ( Figure 3A), thus showing that pheromone receptor genes are useful markers of mating-type identity across a broad range of Pucciniomycotina species.…”
Section: Mat Allele Diversity In the L Scottii Species Complexmentioning
confidence: 65%
“…A complete synteny recovery can be observed outside the left and right boundaries of the P/R locus defined by the genes encoding the PP1/PP2Ac and Prefoldin 3 proteins, respectively (Figure 1). It is currently recognized that pheromone receptor alleles in both Microbotryales and Sporidiobolales have been anciently recruited to the P/R locus and maintained across speciation by balancing selection (Devier et al 2009;Coelho et al 2010). Recent phylogenetic analysis of L. scottii P/R alleles revealed that the same holds true: the STE3.A1 allele sequences were all more similar to the same allele specificity from the distantly related red yeast species than to the alternate conspecific allele (STE3.A2) (de Garcia et al 2015).…”
mentioning
confidence: 99%
“…There is little doubt that the divergence between the A2 and A1 pheromone receptor alleles is ancient (Devier et al 2009). The sequences of these homologs are excessively challenging to align, so recombination between the two mating types in this region must have stopped a very long time ago, perhaps as long as 4 3 10 8 years ago (Devier et al 2009).…”
Section: Evolutionary Stratamentioning
confidence: 99%
“…The sequences of these homologs are excessively challenging to align, so recombination between the two mating types in this region must have stopped a very long time ago, perhaps as long as 4 3 10 8 years ago (Devier et al 2009). If we define "strata" as SR regions with different times since cessation of homologous meiotic recombination, following Lahn and Page (1999), the 4.5-kb region adjacent to the pheromone receptor ( Figure 2A) exhibiting poor alignment with the opposite mating type can be regarded as a remnant of an ancient stratum, similar to the Y chromosome region carrying the mammalian sex-determining SRY locus.…”
Section: Evolutionary Stratamentioning
confidence: 99%
See 1 more Smart Citation